Impact of Foreign Direct Investment and Environmental Regulation on Maritime Sector: Evidence from a Growth Seeking Economy - Aruwei, Porwekobowei; Obasi, Catherine Chimma; Etugbo, Christopher Oghenemaro (Journal of Environmental and Energy Economics, 2025)
The study investigated the effect of foreign direct investment (FDI), environmental regulation on the maritime sector in a growth seeking economy. Data from 2005 to 2023 were used in the study, which were estimated using the error correction technique. The findings showed that environmental regulations negatively affect maritime gross domestic product (GDP) in both the short and longrun. The overall economic activities support maritime GDP both in the long run and the short run. Foreign Direct Investment has no short-term and long run impact. There is a strong adjustment mechanism ensuring maritime GDP realigns with its long-term equilibrium after a shock in the short-term based on the error correction term. The study recommends, based on the findings, that the execution of environmental regulations by policymakers should be gradual. Secondly, they should enhance the utilization of FDI, especially for the maritime sector of the economy. Thirdly, they should make a long-term plan focusing on sustainable environmental practices, capacity building, and technological advancement is critical for the maritime sector's growth and resilience.